Fibrin-specificity of a Plasminogen Activator Affects the Efficiency of Fibrinolysis and Responsiveness to Ultrasound: Comparison of Nine Plasminogen Activators In Vitro - Sakharov, Dmitry V.; Barrett-Bergshoeff, Marrie; Hekkenberg, Rob T.; Rijken, Dingeman C. (Thrombosis and Haemostasis, 1999)
In a number of cases, thrombolytic therapy fails to re-open occluded blood vessels, possibly due to the occurrence of thrombi resistant to lysis. We investigated in vitro how the lysis of hardly lysable model thrombi depends on the choice of the plasminogen activator (PA) and is accelerated by ultrasonic irradiation. Lysis of compacted crosslinked human plasma clots was measured after addition of nine different PAs to the surrounding plasma and the effect of 3 MHz ultrasound on the speed of lysis was assessed.Fibrin-specific PAs showed bell-shaped dose-response curves of varying width and height. PAs with improved fibrin-specificity (staphylokinase, the TNK variant of tissue-type PA [tPA], and the PA from the saliva of the Desmodus rotundus bat) induced rapid lysis in concentration ranges (80-, 260-, and 3,500-fold ranges, respectively) much wider than that for tPA (a 35-fold range). However, in terms of speed of lysis, these three PAs exceeded tPA only slightly. Reteplase and single-chain urokinase were comparable to tPA, whereas two-chain urokinase, anistreplase, and streptokinase were inferior to tPA. In the case of fibrin-specific PAs, ultrasonic treatment accelerated lysis about 1.5-fold. For streptokinase no acceleration was observed. The effect of ultrasound correlated with the presence of plasminogen in the outer plasma, suggesting that it was mediated by facilitating the transport of plasminogen to the surface of the clot.In conclusion, PAs with improved fibrin-specificity induce rapid lysis of plasminogen-poor compacted plasma clots in much wider concentration ranges than tPA. This offers a possibility of using single-or double-bolus administration regimens for such PAs. However, it is not likely that administration of these PAs will directly cause a dramatic increase in the rate of re-opening of the occluded arteries since they are only moderately superior to tPA in terms of maximal speed of lysis. Application of high-frequency ultrasound as an adjunct to thrombolytic therapy may increase the treatment efficiency, particularly in conjunction with fibrin-specific PAs.